(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Learning of the children and their accomplishment is a strong building block in building a stronger and healthier society. The affluence of the nation depends upon the today’s children and their academic accomplishment. The role of parental involvement in children’s education and their achievement has become a central issue in educational policy and research.